Decisive Effects of Life Stage on the Gut Microbiota Discrepancy Between Two Wild Populations of Hibernating Asiatic Toads (Bufo gargarizans) - Song, Xiaowei; Zhang, Jingwei; Song, Jinghan; Zhai, Yuanyuan (Frontiers in Microbiology, 2021)
Until now, the effects of driving factors on the gut microbiota of amphibians are still mostly confounded. Due to a long-term fasting, hibernating amphibians are ideal experimental materials to explore this question. In this study, we characterized the small intestine microbiota of adult hibernating Asiatic toads (Bufo gargarizans) collected from two geographical populations using 16S rRNA amplicon sequencing technique and evaluated the effects of non-dietary factors (e.g., sex and host genetic background). Proteobacteria (0.9196 ± 0.0892) was characterized as the most dominant phylum in the small gut microbiota of hibernating Asiatic toads, among which five core OTUs were identified and three were classified into Pseudomonas. In view of the coincidence between the dominant KEGG pathways (such as the two-component system) and Pseudomonas, Pseudomonas appeared to be a key adaptor for small gut microbiota during hibernation. Furthermore, we detected a greater discrepancy of gut microbiota between geographical populations than between sexes. Both sex and host genetic background showed a minor effect on the gut microbiota variation. Finally, life stage was determined to be the decisive factor driving the gut microbiota discrepancy between populations. However, a large proportion of the gut microbiota variation (∼70%) could not be explained by the measured deterministic factors (i.e., sex, location, body length, and routine blood indices). Therefore, other factors and/or stochastic processes may play key roles in shaping gut bacterial community of hibernating amphibians.